1980
DOI: 10.1001/archneur.1980.00500540075011
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Muscular Atrophy Localized to Arms

Abstract: Twenty-four patients from India, had juvenile muscular atrophy localized to the upper extremities. The condition characteristically affects young men and is not familial. Atrophy is limited to the hand and forearm muscles, with slow progression for two to three years after which it seems to be stationary. The condition is associated with "tremor-like" movements out of proportion to the weakness. Examination of muscle biopsy specimens shows group 2 fiber atrophy. This syndrome, for which no cause has been descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

1984
1984
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(27 citation statements)
references
References 12 publications
2
24
1
Order By: Relevance
“…As a disease entity JLCSMA has been re ported for 30 years, since the first description by Hirayama et al [5], Except for 20 cases reported elsewhere [l-4], most cases have been described in Asians, including 122 cases from Japan [5][6][7][8][9], 102 cases from Sri Lanka [10], 37 cases from India [11,12], 19 cases from Malaysia [13], and 6 cases from Hong Kong [14], Ethnic factors likely exist. How ever, the incidence among Chinese, one of the largest populations, has been strangely rare, comprising only 7 cases from Malaysia [13] and 6 cases from Hong Kong [14], Further more, no case among descendants of Asian immigrants has been reported from the rest of the world.…”
Section: Discussionmentioning
confidence: 99%
“…As a disease entity JLCSMA has been re ported for 30 years, since the first description by Hirayama et al [5], Except for 20 cases reported elsewhere [l-4], most cases have been described in Asians, including 122 cases from Japan [5][6][7][8][9], 102 cases from Sri Lanka [10], 37 cases from India [11,12], 19 cases from Malaysia [13], and 6 cases from Hong Kong [14], Ethnic factors likely exist. How ever, the incidence among Chinese, one of the largest populations, has been strangely rare, comprising only 7 cases from Malaysia [13] and 6 cases from Hong Kong [14], Further more, no case among descendants of Asian immigrants has been reported from the rest of the world.…”
Section: Discussionmentioning
confidence: 99%
“…The disorder, called juvenile-type dis tal and segmental muscular atrophy of upper extremi ties, had such characteristic features that it has become regarded as an established clinical entity [6,7,15,16,18]. In addition, three groups of patients have been reported with clinical involvement other than the distal arm muscles [4,13,20], In Western countries the disorder is rare.…”
Section: Discussionmentioning
confidence: 99%
“…Despite considerable variations in the distribu tion of muscle weakness and wasting, these subtypes of spinal muscular atrophy have much in common: spo radic occurrence; male preponderance; insidious onset; apparent non-progressive course, and lack of involve ment of the cranial nerves, brain stem, pyramidal tracts and sensory system [1,[3][4][5][6][7][8][9][11][12][13][14][15][16][17][18][19][20]. There is an even more localized form where only one limb is affected, most of the patients described being Japanese, Malay sian and Indian [4,6,7,13,15,16,18,20], So far, to our knowledge, only 25 patients have been reported in West ern countries with one limb affected [1,3,5,8,9,11,12,14,17], The present study was undertaken to investigate whether electromyography (EMG) and computed to mography (CT) of the skeletal musculature could offer useful additional information on muscle involvement in monomelic spinal muscular atrophy.…”
Section: Introductionmentioning
confidence: 99%
“…Previous case reports of CFM emanate predominantly from Japan; reports of non-Japanese patients are very rare [2,5,7,39,40,42,45]. However, CFM can be inappropriately treated as entrapment neuropathy, such as cubital tunnel syndrome, mainly due to muscular atrophy of the C7-T1 myotomes, or as a motor neuron disease due to the absence of sensory disturbance.…”
Section: Surgical Indication and Methodsmentioning
confidence: 99%